Knowledge, Attitude and Practice About Epilepsy Among Attendants Of Epilepsy Patients in Bangladesh: A Hospital Based Study - Nath, Dilip Kumar Dev; Ahmed, Rizwan; Nazir, Selina; Marzuk, Riyadh Muhammad; Hoque, Anisul; Hassanuzzaman, Md (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Knowledge and positive attitudes are required for attendants of People With Epilepsy (PWE) to allow them to play their roles efficiently. Knowledge,Attitude and Practice (KAP) study among attendants of PWE was limited in Bangladesh. The study aimed to find KAP of epilepsy among attendants of PWE in a tertiary health center in Bangladesh. Materials and methods: Three hundred and ninety persons accompanying visited or admitted diagnosed cases of epilepsy in different Outpatient and Inpatient Departments of Chittagong Medical College Hospital,Chattogram, Bangladesh, were selected and interviewed with a structured questionnaire. Results: The median age of the respondents was 36 years(Range: 18-78 years), with male to female ratio of 1:1.32.The majority (66.2%) were from rural areas, and only 15.6% had educational qualifications above college level.Overall, 19.7% were knowledgeable (Having fair to good knowledge) about epilepsy, 14.1% had a positive attitude,and 64.9% observed safe practices related to epilepsy.They mostly failed to underline the physical causes of epilepsy, accepted possession as a cause and thought that epilepsy is contagious. Most of them believed that the onset of an epileptic seizure in a spouse is a sufficient reason for divorce. Only 6.7% of the respondents knew how to provide first aid during a seizure attack in the proper way, and 36.2% preferred traditional medicine or spiritual healing for the treatment of epilepsy. Conclusions: The present study revealed poor KAP for epilepsy, which justifies a more structured grassroots-level educational program to raise awareness about different aspects of epilepsy. JCMCTA 2024 ; 35 (1) : 10-15